MODIFIKASI DAN INOVASI OLAHAN KELAPA MUDA MENJADI PUDING DOGAN SEBAGAI PROGRAM MBKM MAHASISWA INDO GLOBAL MANDIRI - Aling Palinggau; Lesi Hertati; Asmawati Asharie (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
Natural resources are resources obtained from nature and can be utilized to meet the needs of human life. Abundant natural resources if not managed properly will be in vain, because this requires a community that is entrepreneurial, creative and innovative in taking advantage of these opportunities. Therefore, I am a UIGM student who wants to make the latest changes and innovations around Km 14 Palembang, namely "Dogan Pudding" which is the basic ingredient of Young Coconut. Activities were carried out around km 14 Palembang. The method I use is a direct method to sell dogan pudding products made from young coconuts. In this product I make new changes and improvements starting from the appearance, taste and others that distinguish it from other dogan pudding products. Compared to other soft drinks, coconut water contains good nutrients classified as very nutritious, hygienic and natural drinks and has been tested many times to cure various diseases. The delicious taste of young coconut and soft texture make young coconut loved by children to adults. Young coconut water has a very good nutritional content for health.